Mirroring minds: assessing the relative stability of self-appraisal and reflected appraisal in daily life - Gütges, Isabel Dorothee; Xi, Haoran; Gauggel, Siegfried; Forster, Saskia Doreen (Frontiers in Psychology, 2025)
IntroductionCultivating a stable self-concept is vital for mental and social well-being. Instability in the processing of self-related information, particularly concerning self-views, have been associated with various mental disorders. Central to the stability of self-perception are two key constructs: self-appraisal and reflected appraisal. Self-appraisal refers to individuals’ personal evaluations of their worth, while reflected appraisal encompasses beliefs about how one is perceived by others. Although previous laboratory studies have examined the formation and impact of self-appraisal and reflected appraisal on self-concept, fluctuations in reflected appraisal relative to self-appraisal in daily life remain largely unexplored. This study aimed to address this gap by examining the variability of both appraisal types and their association with mood changes in everyday contexts.MethodsUtilizing ecological momentary assessment, student participants reported their self-appraisal, reflected appraisal, and mood eight times daily over a ten-day period.ResultsThe analysis revealed that self-appraisal exhibited between-subject (ICC = 0.70) and within-subject (ICC = 0.30) variability. Also, reflected appraisal demonstrated between-subject variability (ICC = 0.72) and within-subject variability (ICC = 0.28). Notably, the results indicated that self-appraisal fluctuated more significantly than reflected appraisal (t = 2.58, df = 98, p = 0.01). Furthermore, a moderate correlation was observed between self-appraisal variability and mood variability (r = 0.45, p < 0.01), whereas the correlation for reflected appraisal variability was weaker (r = 0.35, p < 0.01).DiscussionThese findings underscore the distinct fluctuation patterns of self-appraisal and reflected appraisal in daily life, suggesting that reflected appraisal serves as a stabilizing anchor for self-concept consistency. This study provides a crucial foundation for future research on normative stability within the self-concept framework.